PENGARUH KONEKSI POLITIK, FINANCIAL DISTRESS DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE - Nadila Umairoh (2022)
This study aims to determine the effect of political connections, financial distress and capital intensity on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange in the 2018-2020 period. This research belongs to the type of quantitative research with secondary data in the form of company annual reports. This study used a purposive sampling method with the acquisition of a sampling of 77 samples. The method used in this study is a quantitative research method using secondary data. The analysis technique used is panel data regression analysis using STATA v.12.1. Based on the results of data analysis, it can be concluded that (1) political connections have no effect on tax avoidance, (2) financial distress has a significant positive effect on tax avoidance, and (3) capital intensity has no effect on tax avoidance.